Migration from OAU to AU : exploring the quest for a more effective African peacekeeping capability - Thobane, Bruce N.(Bruce Nchidzi) (Stellenbosch : Stellenbosch University, 2012)
On t.p.: Master of Military Science (Security and Africa Studies (Mil.)).